TECHNOLOGY IMPROVING OF ACCESS TO TRANSPARENT SYSTEMS RESOURCES FOR INTERNET VOTING - Мачалін, І. О.; Комарницький, О. О.; Гнатюк, В. О. (Science-based technologies, 2019)
Remote voting via the Internet provides significant advantages for voters in terms of convenience, mobility, and time savings, but a constraint on its implementation is the distrust of voters due to uncertainty in keeping secrets and fairness in the counting of voting results. It is clear that the staff that manages the counting server has ample opportunities for abuse. Therefore, in order to increase the level of citizens’ confidence in the remote voting system, the challenge is to develop technology that would provide unconditional confidence in the absence of malicious or erroneous actions of personnel in managing the Internet voting system. The article is devoted to the improvement of technology of access of electors within the remote voting system (RVS), which guarantees secrecy of votes and ensures freedom of expression of will in conditions of administrative pressure.The lacks of existent technologies of the controlled from distance access of electors are certain to the server equipment of the transparent (open) voting systems over the Internet. Transparency is that property on that the level of trust of people depends straight. Therefore for providing of transparency of the voting systems it is necessary so to control the actions of personnel in relation to a management a server, that possibility to hide these actions from inspectors was not. With the aim of providing of unimpeded access of electors to the necessary resources and creation of comfortable man-machine interface a model (chart) and corresponding protocol of informative co-operation of automatic search of IP-adress of elements of server equipment are offered at maintenance of queries of electors under time Internet-voting. With the aim of avoidance of long duration delays in access of electors to the resources of the system internet-voting incomposition of her equipment is entered a few servers of search of addresses that function simultaneously and independent of each other. In composition of equipment additional means are entered also is a server-manager that real-time carries out adaptive distribution of stream of appeals between the servers of search of addresses in order to provide the even loading of servers in the conditions of splashes (pulsations) of this stream during voting. With the aim of avoidance of equipment overload by traffic the chart of decision of task of optimal distribution is offered during voting of stream of queries of electors on service between the elements of server equipment.